THE PROCESS OF DIVERSIFICATION AS MANAGEMENT OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS - Небикова, Т.А.; Небиков, М.В. (Modern engineering and innovative technologies, 2023)
The article proposes the concept of diversification, which is used in the literature related to the problems of education. Various types of diversification are summarized. Diversification of the future specialist's education is identified as a pedagogical